The Genetics of Reading Disabilities: From Phenotypes to Candidate Genes - Raskind, Wendy H.; Peter, Beate; Richards, Todd L.; Eckert, Mark A.; Berninger, Virginia W. (Frontiers in Psychology, 2013)
This article provides an overview of (a) issues in definition and diagnosis of specific reading disabilities at the behavioral level that may occur in different constellations of developmental and phenotypic profiles (patterns); (b) rapidly expanding research on genetic heterogeneity and gene candidates for dyslexia and other reading disabilities; (c) emerging research on gene-brain relationships; and (d) current understanding of epigenetic mechanisms whereby environmental events may alter behavioral expression of genetic variations. A glossary of genetic terms (denoted by bold font) is provided for readers not familiar with the technical terms.